2020
DOI: 10.1159/000506712
|View full text |Cite
|
Sign up to set email alerts
|

Resting Left Ventricular Dyssynchrony and Mechanical Reserve in Asymptomatic Normotensive Subjects with Early Type 2 Diabetes Mellitus

Abstract: Background: Most diabetic patients have silent ischemia and cardiac dysfunction that is usually observed in the late phase of the disease when it becomes clinically obvious. We hypothesized that left ventricular dyssynchrony (LVdys) (or dispersion) is an early marker of myocardial involvement in asymptomatic early type 2 diabetes mellitus (T2DM) patients. Therefore, we aimed to detect early markers of myocardial dysfunction in early T2DM using LVdys and left ventricular mechanical reserve (LVMR). Methods: We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…They also claimed that HbA1c, high-sensitivity C-reactive protein and left atrial volume index were inversely correlated with LVMR. This is in line with our study to show the importance of early detection of ventricular dyssynchrony in early stages to detect those diabetic patients who would bene t from early resynchronization therapy (25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also claimed that HbA1c, high-sensitivity C-reactive protein and left atrial volume index were inversely correlated with LVMR. This is in line with our study to show the importance of early detection of ventricular dyssynchrony in early stages to detect those diabetic patients who would bene t from early resynchronization therapy (25).…”
Section: Discussionsupporting
confidence: 92%
“…Divergences(increased PBW) in left ventricular contractibility has been mentioned as the main pathophysiology of LVMD in diabetic patients in the recent studies (24). Many evidences indicate that LVMD is an independent risk factor for further cardiac complications in the diabetic patients (25), therefore, it necessitates detection of LVMD in patients by phase analysis. Despite the fact, phase analysis ability would be much more than the current de nition of LVMD based on QRS width, as 12.5% of our patients had a normal QRS width but an abnormal phase analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that after CS patients achieve biochemical remission, ventricular hypertrophy and systolic function will be partially reversed, but will not return to normal levels. That is, changes in cardiac morphology and function in CS patients can be reversed to a certain extent after biochemical remission of cortisol levels, which is consistent with the conclusion of AHacioglu's team [21] Through in-depth exploration, we found that LVSD, another sensitive index used by STE to evaluate myocardial contractile function, showed signi cant differences between the inactive group and the control group. Since changes in overall left ventricular cardiac function are related to myocardial contractile reserve, as shown by typical contractile reserve markers such as LVEF and GLS, we speculate that CS patients with early subclinical cardiac dysfunction have normal myocardial contractile reserve but abnormal mechanical reserve.…”
Section: Correlation Analysis and Linear Regression Analysis Of Left ...supporting
confidence: 83%
“…Since changes in overall left ventricular cardiac function are related to myocardial contractile reserve, as shown by typical contractile reserve markers such as LVEF and GLS, we speculate that CS patients with early subclinical cardiac dysfunction have normal myocardial contractile reserve but abnormal mechanical reserve. Left ventricular systolic asynchrony can lead to ineffective ventricular pressure work, which in the long run can lead to overall left ventricular systolic dysfunction [21]. Similarly, LVSD can also be present in T2DM patients with normal LVEF and normal myocardial perfusion, and has been shown to be a novel imaging marker for early assessment of myocardial injury [14].…”
Section: Correlation Analysis and Linear Regression Analysis Of Left ...mentioning
confidence: 99%